Analisis Indeks Risiko Genangan Air di Kecamatan Tarakan Barat Kota Tarakan - Rahmat Faizal; Zikri Alstony (Borneo Engineering : Jurnal Teknik Sipil, 2022)
Almost every year the city of Tarakan experiences problems regarding standing water during the rainy season, especially in the West Tarakan sub-district which is the center of Tarakan City. This puddle not only submerged settlements and offices but also shops and road access which caused considerable economic losses. This can be overcome by analyzing the risk of waterlogging where each area has a different level of vulnerability. The purpose of this study is to determine high, medium, and low risk areas for standing water in the Drainage Area of West Tarakan District, Tarakan City. The research implementation method includes data collection (institutional and field surveys), analyzing the index of vulnerability, vulnerability and capacity and analyzing the flood risk map. The index analysis is carried out through simulated parameter score analysis. Based on the results of the analysis of the research data, it can be concluded that the water inundation risk index in the West Tarakan District is as follows, the sub-districts that are on the highest risk index are Karang Anyar sub-district, then Karang Rejo village, kelurahan Karang balik and Kelurahan Karang Newar Pantai Nerda is at index 2 or is at a moderate risk index, then the kelurahan that has the lowest risk index is Hope Reef with a risk index of 1